Eco-Friendly and Cyclical Bioeconomy - Sanjaiy S. S.,; Vaishnavi N., (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Silk production, or sericulture, has a long and illustrious history that dates back more than five thousand years. The sericulture industry, which starts with the cultivation of mulberry trees and their many applications, including the production of leaves for silkworm food, promotes employment, economic growth, and health. High-quality silk thread and high-protein food for both humans and animals are the products of sericulture. With other advantages ranging from improving human health to conserving soil, it relies on one of the most adaptable plants known. When supply chain management is done carefully, sericulture is a unique end-to-end sustainable sector with no ecological impact. Silk is a naturally occurring polymer called poly-fibroin that has the benefits of biodegradability and plastic plasticity.Therefore, we may imagine a sustainable silk-derivatives business that encourages the use of fibroin-derived compounds in place of petrochemicals in a variety of applications, from sophisticated biopharmaceuticals and implants to commonplace everyday health and wellness goods.
Keywords: Bioeconomy; Circular Economy; Sustainable Development; Renewable Resources; Environmental Sustainability